PENGARUH PEMBERIAN MINUMAN JELI SARI BUAH JAMBU BIJI DAN JERUK TERHADAP PENURUNAN KADAR ASAM URAT DARAH PADA USIA 40 TAHUN KEATAS - Afiyah, Nurul; Wijaningsih, Wiwik; Prihatin, Setyo; Susiloretni, Kun Aristiati (Poltekkes Kemenkes Semarang, 2018)
Background : Hyperuricemia is a condition where blood uric acid levels above normal. The Puskesmas Tlogosari Wetan has 5 hyperuricemia patients. Although a little but still needed a treatment to prevent complications, that is with eating foods high vitamin c for reduce uric acid levels. Objective : to determine the effect of jelly drinks guava and orang juice to a decrease in blood uric acid levels at 40 years above. Methode :The research type was Quasi Experiment research and used Randomized Pretest Posttest Control Group Design. The sampling is randomly, 17 treatment samples and 17 control samples. Independent T-test was used to analyze the differences of blood uric acid levels between the treatment group and the control group. Results : There were significant effect in blood uric acid levels (p=0.001) between treatment group and control group with decrease of 0,42 mg/dl and 1,58 mg/dl. Conclusion : Consumption of jelly drinks guava and orange juice for 14 days and nutritional counseling about hyperuricemia can lower blood uric acid level in 40 years above, statistically insignificant.